Letter to CSU Northridge from Robert Chianese - Chianese, Robert; Sustainability Council of Ventura County (Sustainability Council of Ventura County)
Robert Chianese writes a letter to CSU Northridge requesting reimbursement for expenses on the California Urban Environmental Research and Education Center (CUEREC) funded project. Council worked on the Final Report since February 2001 and did a power point presentation event in Oxnard. With translation and printing fees the total is $1,950.00.